Strengthening Character Education Through Holistic Learning Values (QUALITY, 2022)
The reality of moral degradation among students today, among others, can be seen from the fading of politeness and manners and behaviour bullying toacademic cheating. This reality requires the response of various parties to re-strengthen character education. Families and educational institutions are strategic places to grow character values together. This study aims to describe and analyze forms of strengthening character education through holistic learning values. The research focuses on the implementation of learning, the use of the learning environment, the synergy of families, schools, and communities, and the principles of strengthening character education. This research approach uses descriptive qualitative with a moderate participation role. Data collection techniques with structured interviews, participatory observation, and documentation. At the data analysis and interpretation stage, researchers used literature analysis, centralized discussion, and focus group discussion. The study results show that forms of synergy between schools, families, and communities are needed to strengthen character education through holistic learning. Teachers should be able to act as parents as well as friends for students while at school. Stakeholders and related agencies need cooperation between educational institutions, revitalizing the role of school committees, empowering graduates, the potential for local wisdom in the academic environment, and outreach to school programs through various forums and media. Parental support is needed for the educational process and student learning progress, as well as periodic monitoring and evaluation of education involving multiple related parties. Holistic learning requires the teacher's understanding of integrated learning and strives for meaningful learning. Integration of religion and science curriculum is also needed as integrative learning so that students can develop their potential well. Penguatan Pendidikan Karakter Melalui Nilai-Nilai Pembelajaran Holistik. Realitas degradasi moral dikalangan pelajar saat ini, diantaranya tampak dari mulai lunturnya kesantunan dan tata krama, perilaku bullying hingga kecurangan akademik. Realitas tersebut membutuhkan respon pelbagai pihak untuk kembali melakukan penguatan pendidikan karakter. Keluarga dan lembaga pendidikan menjadi tempat yang strategis untuk bersama menyemai nilai-nilai karakter. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis bentuk-bentuk penguatan pendidikan karakter melalui nilai-nilai pembelajaran holistik. Fokus Penelitian pada pelaksanaan pembelajaran, pemanfaatan lingkungan pembelajaran, sinergitas keluarga, sekolah dan masyarakat serta prinsip-prinsip penguatan pendidikan karakter. Pendekatan penelitian ini menggunakan kualitatif deskriptif dengan peran partisipasi moderat. Teknik Pengumpulan data dengan wawancara terstruktur, observasi partisipatif dan dokumentasi. Pada tahap analisis data dan pemaknaan, peneliti menggunakan analisis literatur, diskusi terpusat serta focus group discussion. Hasil penelitian menunjukkan bahwa diperlukan bentuk-bentuk sinergitas antara sekolah, keluarga dan masyarakat dalam menguatkan pendidikan karakter melalui pembelajaran holistik. Guru hendaknya dapat berperan sebagai orang tua sekaligus sahabat bagi siswa selama berada di sekolah. Diperlukan kerjasama yang baik antara lembaga pendidikan dengan stakeholders dan dinas terkait, revitalisasi peran komite sekolah, pemberdayaan lulusan, potensi kearifan lokal di lingkungan pendidikan, sosialisasi program sekolah melalui berbagai forum dan media. Diperlukan dukungan orang tua terhadap proses pendidikan dan kemajuan belajar peserta didik, serta melakukan pengawasan dan evaluasi pendidikan secara berkala yang melibatkan berbagai pihak terkait. Pembelajaran holistik memerlukan pemahaman guru terhadap konsep pembelajaran terpadu serta mengupayakan pembelajaran yang memiliki kebermaknaan. Diperlukan pula Integrasi kurikulum agama dan sains serta pembelajaran integratif agar peserta didik dapat mengembangakan potensi dirinya dengan baik.